2016
DOI: 10.1016/j.janxdis.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Does ‘fear of dying’ indicate a more severe presentation of panic disorder?

Abstract: reporting FOD (n=153) were compared to patients denying FOD (n=178) on variables indicating PD severity (e.g., number of symptoms) and psychiatric impairment (e.g., hospitalizations). PD patients with FOD reported a greater number of panic symptoms, agoraphobia diagnoses, and were more likely to be seeking treatment primarily for PD. We found no clinical impairment or comorbidity differences between groups. Results suggest that panic attacks with FOD are related to a more acute presentation of PD. Such results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Individuals with panic disorder experience higher levels of death anxiety compared to individuals with depression and social phobia. Previous studies evaluating the role of death anxiety in panic disorder have indicated that death anxiety is a significant symptom in severe panic attacks, and the presence of death anxiety during panic attacks indicated greater number of reported panic attacks, avoidance behaviors and more frequent diagnosis of agoraphobia (Craske et al 2010, Gazarian et al 2016. In conclusion, individuals with various psychological disorder symptoms have higher levels of death anxiety compared to non-clinical control groups and the death anxiety may play a role at different levels in different psychological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with panic disorder experience higher levels of death anxiety compared to individuals with depression and social phobia. Previous studies evaluating the role of death anxiety in panic disorder have indicated that death anxiety is a significant symptom in severe panic attacks, and the presence of death anxiety during panic attacks indicated greater number of reported panic attacks, avoidance behaviors and more frequent diagnosis of agoraphobia (Craske et al 2010, Gazarian et al 2016. In conclusion, individuals with various psychological disorder symptoms have higher levels of death anxiety compared to non-clinical control groups and the death anxiety may play a role at different levels in different psychological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of intense fear may be an essential determinant in differentiating between abdominal distress associated solely with PAs and GI diseases. Those experiencing panic symptoms, including abdominal distress, frequently report fear of losing control or dying ( 204 , 205 ). Such fears are seldom reported by GI patients, who typically report pragmatic fears such as not having access to a toilet or losing bowel control ( 206 ).…”
Section: Nausea or Abdominal Distressmentioning
confidence: 99%
“…Gazarian et al. ( 205 ) noted that Hispanic patients report a greater fear of dying when having PAs. Patients from minority groups are more likely to express symptoms and distress conveyed uniquely in their culture ( 291 ).…”
Section: Cultural Considerationsmentioning
confidence: 99%